Firm Value with Political Connections and Institutional Ownership as Moderation - Ni Made Ananda Saraswati; Yeney Widya Prihatiningtias; Lilik Purwanti (Postgraduate Program Merdeka University, 2024)
This research aims to analyze the effect of CEO power, CEO duality, and CEO busyness on firm value with the moderating role of political connections and institutional ownership. This study uses panel data regression analysis and Mode-rated Regression Analysis (MRA) methods. The research population is 440 energy companies on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Purposive sampling technique is used to select the research population based on certain criteria so that a total research sample of 180 companies is found. Quantitative data is taken from the company’s annual report and analyzed using Econometric Views (EViews). This study found that CEO power has a positive effect on firm value. Furthermore, this study also found that CEO duality and CEO busyness have a negative effect on firm value. Then, political connections and institutional owner-ship can moderate the effect of CEO duality and CEO busyness on firm value. This study provides additional empirical evidence on agency theory. In addition, this study recommends that corporate leaders can increase their stock ownership, as well as suppress duality, busyness, and political connections in order to create positive firm value. JEL Classification: G32, G34, O53 DOI: https://doi.org/10.26905/afr.v7i3.15322